2019
DOI: 10.1101/822635
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cerebellar lesions disrupt spatial and temporal visual attention

Abstract: 2 Cerebellar contributions to spatial and non-spatial attention ABSTRACTThe current study represents the first comprehensive examination of spatial, temporal and sustained attention following cerebellar damage. Results indicated that, compared to controls, cerebellar damage eliminated the onset of inhibition of return (IOR) during the reflexive covert attention task, and reduced the ability to detect successive targets during an attentional blink task.However, cerebellar damage had no effect on voluntary cover… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…The rationale behind this investigation was the potential functional association between damaged cerebellar regions and the dorsal and ventral attentional networks. The study revealed that patients with cerebellar damage exhibited impairments in the allocation of spatio-temporal attention (Craig et al, 2021). In a similar vein, Wang et al (2021) enrolled 36 patients with posterior cerebellar infarction and 30 healthy volunteers for cognitive neurofunctional assessment and MRI scans to extract parameters related to the structural topological features of brain networks.…”
Section: Cerebellum and Attentional Functionmentioning
confidence: 94%
See 1 more Smart Citation
“…The rationale behind this investigation was the potential functional association between damaged cerebellar regions and the dorsal and ventral attentional networks. The study revealed that patients with cerebellar damage exhibited impairments in the allocation of spatio-temporal attention (Craig et al, 2021). In a similar vein, Wang et al (2021) enrolled 36 patients with posterior cerebellar infarction and 30 healthy volunteers for cognitive neurofunctional assessment and MRI scans to extract parameters related to the structural topological features of brain networks.…”
Section: Cerebellum and Attentional Functionmentioning
confidence: 94%
“…These findings suggest that lesions in the cerebellum can specifically impair the orienting function of the attentional network. Craig et al (2021) conducted a study examining attentional function in 14 patients with cerebellar infarction. The rationale behind this investigation was the potential functional association between damaged cerebellar regions and the dorsal and ventral attentional networks.…”
Section: Cerebellum and Attentional Functionmentioning
confidence: 99%
“…2 Previous studies revealed the engagement of the cerebellum in a variety of processes, including motor functions such as maintaining body equilibrium, controlling muscle tension, and coordinating deliberate movements, as well as cognitive activities, emotional experiences, and social interactions. 3,4 Damage to the cerebellum frequently leads to impairment, which impacts (i) the visuospatial abilities, attention, in particular focusing attention on space and time; 5 (ii) executive functions such as inhibitory control, cognitive flexibility, planning, reasoning, and decision-making; 5−9 (iii) the working memory affecting comprehension, reading, and learning; 2 (iv) language skills, including issues related to the timing, adaptation, prediction, planning, fluency, grammar, or even speech disruptions. 2 Also, the cerebellar dysfunctions induced by modifications at the molecular level 10 represent the basis of the common pathological conditions such as Parkinson's disease (PD), 11 Huntington disease (HD), 12 Alzheimer's disease (AD), 13 and multiple sclerosis (MS).…”
Section: Introductionmentioning
confidence: 99%